Implementing the Quizizz Application in Improving Students' Grammar Skills - Wali, Asmaul Husna; Meristika Moatia (English Lecturers and Teachers Association (ELTA), 2025)
This study, conducted at SMA Negeri 9 Aceh Barat Daya with 60 students, investigated the effectiveness of Quizizz, a digital gamification tool, in improving students’ grammar skills. Employing a quasi-experimental design, the research involved two groups: an experimental group using Quizizz and a control group taught through conventional methods, each consisting of 30 students. Both pre-tests and post-tests were administered, and the data were analyzed using the Shapiro-Wilk test, Levene’s test, and a paired-samples t-test. The normality and homogeneity tests confirmed that the data met the assumptions for parametric analysis. The paired-samples t-test revealed a greater increase in scores for the experimental group (9.83) compared to the control group (5.20), indicating a significant improvement in grammar mastery for both groups, with the experimental group outperforming the control group. The use of Quizizz offered several benefits, including increased student engagement, immediate feedback, and an interactive, competitive learning environment, all of which contributed to enhanced motivation and a deeper understanding of grammar concepts. Therefore, these results confirm that Quizizz can be an effective and engaging alternative to conventional grammar instruction, improving both learning outcomes and student enthusiasm.